Walking meditation versus balance training for improving balance abilities among older adults with history of fall: A randomized controlled trial - Chalida Phoobangkerdphol (2022)
Objective: To investigate improvement in balance abilities compared between walking meditation and balance training among older adults with history of fall. Interventions: Walking meditation or mindfulness meditation whilst standing and moving (n = 35) or balance training (n = 33) 20–30 min/day, 5–7 days/week for 24 weeks was performed at home. Main outcomes: The primary outcomes were dynamic balance abilities as assessed by Timed Up and Go test (TUGT), and static balance as assessed by Functional Reach Test (FRT) and Single Leg Stance Test (SLST). The secondary outcomes were quality of life as measured by the EuroQOL 5-dimensions 5-levels (EQ-5D-5L), and mental health as evaluated by the Thai Geriatric Mental Health Assessment Tool-15 (TGMHA-15). All outcomes were assessed at baseline, 6 months, and 9 months. Self-reported compliance, adverse events, and patient satisfaction were recorded at 6 and 9 months. Results: The mean age was 69 years (range: 60–85). No significant difference was observed between groups for the 3 primary outcome measures. The mean difference (95% confidence interval) between groups was −0.48 (-1.40, 0.44) for TUGT, −1.11 (-3.66, 1.45) for FRT, and 0.82 (-5.03, 6.67) for SLST. The EQ-5D-5L and TGMHA-15 also showed no significant difference between groups. Most participants were in good compliance with the exercise protocol (48.3–68.0%), and no serious adverse events were reported. Conclusion: Our results showed walking meditation to be comparable to balance training for improving balance abilities in older adults with history of fall. Walking meditation may be considered an alternative treatment for improving balance abilities in this patient population.